Terror Bomb Hits Nagasaki (Journal and Tribune Co., 1945)
Front page of the August 9, 1945 issue of The Knoxville Journal with the headline "Terror Bomb Hits Nagasaki." The page has articles relating to the dropping of the second atomic bomb on Nagasaki; and Japan and Soviets attacking the Japanese in Manchukuo, now known as Manchuria. Notably, racist ethnic slurs are used to refer to the Japanese in a featured article. The use of these words reflects the heightened anti-Japanese sentiments that were fueled by World War II.
Keywords: China--Manchuria; Atomic bomb; Japan; World War (1939-1945); Nuclear weapons; Racism; Racism in mass media; Newspapers; Tennessee--Knoxville